2018
DOI: 10.1021/acs.jpcc.8b08566
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer, Bilayer, and Heterostructures of Green Phosphorene for Water Splitting and Photovoltaics

Abstract: We report the results of density functional theory (DFT) based calculations on monolayer and bilayer green phosphorene and their heterostructures with MoSe2. Both monolayer and bilayer green phosphorene are direct band gap semiconductors and possess anisotropic carrier mobility as high as 10 4 cm 2 V -1 s -1 . In bilayers, pressure of about 9 GPa induces the semiconductor-metal transition. Moreover, the band gap depends strongly on the thickness of the films and the external electric field. By employing strain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 44 publications
6
46
2
Order By: Relevance
“…[32][33][34][35] Following the fact nding journey, many other allotropes/ polytypes of phosphorene viz., red, black, violet, green phosphorene have been realized [36][37][38][39] and some of them have been explored for water splitting application. [40][41][42][43] More recently, a new member of phosphorene polytype was realized through the synthesis of mono-layered honeycomb buckled bluephosphorene (B-phosphorene) on an Au (111) sheet using a molecular beam epitaxial method with black-phosphorous as precursor. 44 It has been reported that a specic dislocation in black phosphorene induces a new structure with zigzag puckering, called B-phosphorene with a characteristic tunable bandgap upto 2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Following the fact nding journey, many other allotropes/ polytypes of phosphorene viz., red, black, violet, green phosphorene have been realized [36][37][38][39] and some of them have been explored for water splitting application. [40][41][42][43] More recently, a new member of phosphorene polytype was realized through the synthesis of mono-layered honeycomb buckled bluephosphorene (B-phosphorene) on an Au (111) sheet using a molecular beam epitaxial method with black-phosphorous as precursor. 44 It has been reported that a specic dislocation in black phosphorene induces a new structure with zigzag puckering, called B-phosphorene with a characteristic tunable bandgap upto 2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in FIG.4(b), the work function was in the range of 4.64˜6.02 eV for the ZGPNRs with the pristine ribbons having the lowest values. The calculated work function for the 2D monolayer of GP was 5.25 eV [41]. Since a controlled work function helps to promote the efficiency of charge transportation and photovoltaic conversion, the ZGPNRs are expect to have potential applications in photoelectro-catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…After the discovery of graphene, there have been significant advances in synthesis and characterization of novel 2D materials, including Boron based (h-BN, borophenes) [ 28 ], Group IV (Silicene, Germanene, Stanene) [ 29 ], Group V (Phosphorene, Arsenene, Antimonene) [ 30 ], Group IVA-VIA (SnO, SnS 2 , SnSe 2 ) [ 31 ], Group III-IV (GaS, GaSe) and Transitional Metal-based (Metal Carbides, Mxenes) and 2D perovskites materials [ 32 ]. Subsequently, the research into these 2D materials and their composites and heterostructures for photocatalytic water-splitting has been initiated by researchers [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%